Pembelajaran Sejarah di Era Digital: Strategi Pengembangan Bahan Ajar Efektif Bagi Generasi Z - Mahlaini; Fanisa Putri Anggraini; Chardinal. DV; Sani Safitri; Rani Oktapiani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
The rapid advancement of digital technology has transformed the learning patterns of Generation Z, who tend to be visual, quick in accessing information, and highly engaged with interactive media. These characteristics pose challenges for history learning, which is often perceived as monotonous and focused on memorization. This study aims to examine the needs, urgency, and strategies for developing history teaching materials that are relevant and effective for Generation Z in the digital era. Using a descriptive qualitative approach through library research, the findings indicate that effective history materials should integrate digital media, apply active learning models, and connect historical content with students’ real-life experiences. Teachers play a key role as innovators by utilizing digital storytelling, virtual tours, gallery walks, and gamification. Integrating local history and national values is also essential to strengthen students’ national identity. This study emphasizes that developing digital history teaching materials is not merely about adopting technology but about creating meaningful, reflective, and generation-appropriate learning experiences.